2015
DOI: 10.3916/c44-2015-19
|View full text |Cite
|
Sign up to set email alerts
|

Categorization, Item Selection and Implementation of an Online Digital Literacy Test as Media Literacy Indicator

Abstract: This paper aims to measure a population’s level of knowledge and active use of certain digital tools that play a primary role in developing their media literacy. To achieve it, an Online Digital Literacy test was designed to measure the knowledge and active usage of 45 different online software packages. This tool works as a reliable indicator to identify a population’s media literacy development in terms of its linguistic and technological dimensions. More than 1,500 subjects of different gender, age and leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
0
6
0
12
Order By: Relevance
“…The current conceptualizations on the digital divide result insufficient for finding the reasons why two individuals who have the same degree of digital autonomy and literacy can obtain very different benefits when using the Internet. In this sense, the development of a theoretical framework that is well cemented and that brings to light the relationship between different uses of the Internet and its benefits, has been suggested (Dornaleteche et al, 2015;Blank and Groselj, 2014;Van Deursen and Helsper, 2015). Even though this topic is not analyzed in depth in this study, it does takes into account the use given to the Internet by the students when conducting academic tasks.…”
Section: Digital Divide and The Levels Of Access To Internet Usementioning
confidence: 98%
“…The current conceptualizations on the digital divide result insufficient for finding the reasons why two individuals who have the same degree of digital autonomy and literacy can obtain very different benefits when using the Internet. In this sense, the development of a theoretical framework that is well cemented and that brings to light the relationship between different uses of the Internet and its benefits, has been suggested (Dornaleteche et al, 2015;Blank and Groselj, 2014;Van Deursen and Helsper, 2015). Even though this topic is not analyzed in depth in this study, it does takes into account the use given to the Internet by the students when conducting academic tasks.…”
Section: Digital Divide and The Levels Of Access To Internet Usementioning
confidence: 98%
“…Likewise, some works have approached the assessment of media competence in preschool education by means of a questionnaire that allows three levels of competence to be established: excellent, acceptable and minimum (García, Duarte, & Guerra, 2014). The on-line digital literacy test (ADO) has also been proposed as an indicator of media competence (Dornaleteche, Buitrago, & Moreno, 2015). It was applied to citizens whose results and general conclusions indicated that the level of on-line digital literacy of the average citizen was unfavourable.…”
Section: Assessment Of Digital Competence: Previous Studies and Currementioning
confidence: 99%
“…En cualquier caso, y como ya señaláramos en anteriores publicaciones, "después de años de discusión terminológica parece ya casi incuestionable que la educación mediática engloba una serie de alfabetizaciones que van más allá de la adquisición de la tan ansiada competencia digital; pero que, de alguna manera, el dominio del campo abierto por la era digital sigue siendo uno de los pilares fundamentales sobre los que se asienta la educomunicación del siglo XXI" (Dornaleteche, Buitrago y Moreno, 2015).…”
Section: A Modo De Propuestaunclassified